If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8X + -4p + -5x = 0 Solving 8X + -4p + -5x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4p' to each side of the equation. 8X + -4p + 4p + -5x = 0 + 4p Combine like terms: -4p + 4p = 0 8X + 0 + -5x = 0 + 4p 8X + -5x = 0 + 4p Remove the zero: 8X + -5x = 4p Add '5x' to each side of the equation. 8X + -5x + 5x = 4p + 5x Combine like terms: -5x + 5x = 0 8X + 0 = 4p + 5x 8X = 4p + 5x Divide each side by '8'. X = 0.5p + 0.625x Simplifying X = 0.5p + 0.625x
| 8x-12=5x+25 | | 8.1(4.6)= | | 2x+19=9x+6 | | 2x-3+6x-8=5x+4 | | 4/5=9/10 | | 5v-4.2=8.3 | | p-(17)=-23 | | -11x=-6 | | 2x^2=0.08 | | -5/8=3/4=5/8 | | 59=-x/8 | | 4x=a-6 | | 15(x)+85(y)=2556 | | 3(1+-1y)=8+(-5y) | | x^3-6x^2-15x+40=0 | | -5=-27w | | -w/9=-50 | | -2w+5(w-2)=-19 | | -39=3(v+3)+5v | | 9x+4y=10 | | 1/4x1/4x1/4x1/4 | | 3m-12=3(8m+3) | | 8m^2+72m-16=0 | | 5(2z-1)-5(z+9)=2(z+1) | | 3(4a+5)=3+6a | | 6-6n=6(6n+1) | | 2x^2-25x-54=0 | | -7+5x=-7(1+8x) | | 7x-8y=-18 | | ^4√(((3x^8)(y^2))/(8x^2)) | | P^2=81/100 | | 1+2b=-(-5b-8)-2b |